PENGARUH PENERAPAN SISTEM KEUANGAN DAERAH, TRANSPARANSI, AKTIVITAS PENGENDALIAN DAN PENYAJIAN LAPORAN KEUANGAN TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH (Studi pada Satuan Kerja Perangkat Daerah Kabupaten Indragiri Hilir) - Angraini, Dewi Yuli; Agusti, Restu; Anggraini, Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
Accountability of a province financial management is a processes of finance started from plan, action, report, responsibility and supervise which can be really reported and been responsible to society and DPRD (Representatives of province). The type of data in the research is quantitative. The population in the research is SKPD in Riau Provincial Government, Indragiri Hilir district. Data those are used are primary data. The method of collecting data by sharing questionnaire. The researcher uses double regression analysis by using t-test. The result of the study showed that the implementation of the financial system, transparency, the activity of control, and the presentation of financial report have a significant affect accountability in financial management. The determination koefisien in this study 60,4% while 39,6% was influenced by other variable.eKeywords: accountability, financial, management, control, and financial report.